Mineral Composition of Herbaceous Species Seseli rigidum and Seseli pallasii: a Chemometric Approach - Marija D. Ilic; Violeta D. Mitić; Snežana B. Tošić; Aleksandra N. Pavlović; Marija S. Marković; Gordana S. Stojanović; Vesna P. Stankov Jovanović (Acta Chimica Slovenica, 2021)
Nutrients play an essential role in many metabolic processes whose deficiency or excess can be harmful to the plant itself and through the food chain to both animals and humans. Medicinal plants used in the food and pharmaceutical industries can be contaminated with increased concentrations of heavy metals. The plant species Seseli rigidum and Seseli pallasii from the Balkan Peninsula are used in traditional medicine and spices in the diet, so it was necessary to determine the mineral composition to ensure their safe application. In this work, the mineral composition was determined in medicinal species of the genus Seseli using inductively coupled plasma with optical emission spectrometry (ICP-OES). Two multivariate statistic methods –principal component analysis (PCA) and hierarchical cluster analysis (HCA) were applied to distinguish samples regarding their mineral composition. The mineral composition of both studied species is following the literature data. The results obtained using multivariate statistics methods agree and distinguish certain parts of the tested plants based on the highest content of micro, macro, or trace elements.